An Analysis of Young Clients' Communications About Their Suicidality on a Text Message Helpline: “I'm Scared of What I Might Do to Myself” - Van Wyk, Jeanne; Gibson, Kerry (Frontiers in Psychiatry, 2022)
Background: Youth suicide is a major international concern and prevention is a priority. In most cases suicidal behaviour would be preceded by a period of suicidal ideation. Although feeling suicidal is recognised as a risk factor for suicide, there is little research which captures young people’s own experience of suicidality in a moment of crisis. Aims: This study aimed to explore young people’s own accounts of their suicidality in the moment in which they experienced it. Method: This qualitative study examined clients’ experience of suicidality as communicated during a text message helpline counselling interaction. The data consisted of 125 text transcripts of an interaction during which a client was experiencing suicidality. These were obtained from a New Zealand based youth helpline service. The data was analysed using thematic analysis. Findings: The analysis showed that clients’ experienced suicidality as a normal part of their life; that it was understood as a form of coping and that it was seen as a legitimate way to communicate distress. Clients described rapid fluctuations in the intensity of their suicidality and a feeling of being out of control. Despite this, they also communicated ambivalence about acting on their suicidality, and a recognition of the need to get help. Conclusions: This study offered unique insights into young people’s experience of suicidality and opens up opportunities for prevention. It underlines the importance of identifying chronic suicidality early and providing intervention and support prior to a suicidal crisis. The findings also highlight the importance of having 24-hour access to crisis support that can provide young people with the help they are looking for and ally with the part of them that wishes to live.